Perception of career barriers: The importance of gender and ethnic variables - Cardoso, Paulo (2009)
Differences of gender and ethnicity were examined in terms of the perception of barriers to career development. Both an inquiry of demographic data and the revised version of the Perception of Career Barriers Inventory (IPBC) were administered to a sample of 457 ninth grade students in Portuguese public schools. Results suggest that, among youngsters 14-15 years old, gender and ethnicity representations of group identity play a role in career development. Across all IPBC scales, girls present higher means than boys and the former take both Sexual Discrimination and Role Conflict as the most important barriers to career development. In what concerns the ethnic group, the means of the African participants are higher than the Portuguese ones across all the IPBC scales. Among Africans, General Discrimination, Sexual Discrimination and Ethnic Discrimination are the most expected barriers. This expectation is more emphasized with African participants born in Africa than with those born in Portugal. Theoretical and practical implications of the results for contextualized interventions with minority groups in Portuguese schools are examined in the light of their respective socialization processes.